Scaling Up Clean Cooking Solutions : The Context, Status, Barriers and Key Drivers - Ekouevi, Koffi (International Finance Corporation, Washington, D.C., 2017)
The nexus of improved energy access, direct health benefits and reduced indoor air pollution can be achieved in part through expanding access to clean cookstoves and fuels. This is of particular significance to approximately three billion people, mainly in South Asia and Sub-Saharan Africa, who still rely on solid fuels (traditional biomass and coal) for cooking and heating. Large-scale adoption and sustained use of clean cookstoves is not materializing due to a variety of context specific barriers both on the consumer and producer/distributor sides. While financing in terms of a lack of investment and working capital appear to be constraints for producers, lack of information, awareness, and cultural barriers dominate for consumers and should not be underestimated. Addressing these challenges requires a multi-pronged approach across four key drivers that have been identified through reviewing successful programs: awareness raising; markets and preferences; technologies and standards; and innovative financing.